The role of immunotherapy in resectable non-small-cell lung cancer - Conor D. Moloney; Patrick M. Forde (Therapeutic Advances in Medical Oncology)
Non-small-cell lung cancer (NSCLC) accounts for 80%–85% of all lung cancer cases, being the leading cause of cancer-related mortality worldwide. Historically, outcomes for patients with resectable disease have trailed those with other solid organ malignancies. Advances in treatment strategies, particularly in immunotherapy (IO), have revolutionised the landscape of lung cancer care. In resectable NSCLC (rNSCLC), including stage III disease, the integration of immunotherapy is increasingly being explored for its potential to reduce recurrences and improve survival outcomes. Several landmark clinical trials have resulted in regulatory approvals, and the rapid adoption of immunotherapy in the neoadjuvant, perioperative and adjuvant settings. This review will comprehensively examine the evolving role of immunotherapy in rNSCLC, with a focus on trial evidence, mechanisms of action, biomarkers and challenges in clinical implementation. We also discuss its implications for multimodal therapy across neoadjuvant, perioperative and adjuvant settings while highlighting potential future directions and identifying unanswered questions.